Amelioration of metabolic disorders by a mushroom-derived polyphenols correlates with the reduction of Ruminococcaceae in gut of DIO mice - Li Sun; Li Bao; Dorji Phurbu; Shanshan Qiao; Shanshan Sun; Yangzom Perma; Hongwei Liu (Food Science and Human Wellness)
A polyphenolic alkaloid-enriched extract (PAE) was prepared from the fruiting bodies of a wild edible mushroom Sarcodon leucopus. Oral administration of PAE reduced hyperglycemia, hyperlipidemia, hepatic steatosis, and LPS-related inflammation in high fat diet-induced obese (DIO) mice. Furthermore, we show that PAE produces taxonomic and predicted functional changes in the gut microbiome of DIO mice. A significant decrease in the family of Ruminococcaceae, especially the secondary bile acid-producing bacteria of Intestinimonas and Anaerotruncus, is detected in the gut microbiome of PAE-treate mice. Accordingly, reductions of deoxycholic acid and lithocholic acid are found in the feces of PAE-treated DIO mice, which benefits for the intestinal integrity and the reduction of inflammation. A gut microbiota related mechanism for the anti-metabolic syndrome effects of the PAE is proposed. We suppose the polyphenolic alkaloid extract from S. leucopus be a new and beneficial prebiotic regulating glucose and lipid metabolisms.